Cancer Prevalence in Aichi, Japan for 2012: Estimates Based on Incidence and Survival Data from Population-Based Cancer Registries - Nakagawa-Senda, Hiroko (Asian Pac J Cancer Prev, 2017)
BACKGROUND: Cancer is the leading cause of death among both men and women in Japan. Monitoring cancer prevalence is important because prevalence data play a critical role in the development and implementation of health policy. We estimated cancer prevalence in 2012 based on cancer incidence and 5-year survival rate in Aichi Prefecture using data from a population-based cancer registry, the Aichi Cancer Registry, which covers 7.4 million people. METHODS: The annual number of incident cases between 2008 and 2012 was used. Survival data of patients diagnosed in 2006–2008 and followed up until the end of 2012 were selected for survival analysis. Cancer prevalence was estimated from incidence and year-specific survival probabilities. Cancer prevalence was stratified by sex, cancer site (25 major cancers), and age group at diagnosis. RESULTS: The estimated prevalence for all cancers in 2012 was 68,013 cases among men, 52,490 cases among women, with 120,503 cases for both sexes. Colorectal cancer was the most incident cancer with 6,654 cases, accounting for 16.0% of overall incident cases, followed by stomach cancer with 5,749 cases (13.8%) and lung cancer with 5,593 cases (13.4%). Prostate cancer was the most prevalent among men, accounting for 21.5%, followed by colorectal and stomach cancers. Breast cancer was the most prevalent among women, accounting for 28.6%, followed by colorectal, stomach, and uterine cancers. CONCLUSION: This study provides cancer prevalence data that could serve as useful essential information for local governments in cancer management, to carry out more practical and reasonable countermeasures for cancer.